If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7g = 26 + 5g Solving 7g = 26 + 5g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-5g' to each side of the equation. 7g + -5g = 26 + 5g + -5g Combine like terms: 7g + -5g = 2g 2g = 26 + 5g + -5g Combine like terms: 5g + -5g = 0 2g = 26 + 0 2g = 26 Divide each side by '2'. g = 13 Simplifying g = 13
| 5(x+3)=3x+7 | | 9(x+2)=63 | | -3(2x-1)+5x=3-x | | 18=2(r-3) | | x2+1/6x=0 | | 12+m-6=3m-4m | | -17+5x=3x+33 | | -152-6x=46+5x | | 3a+4b+5c= | | -47+6x=33+11x | | -68+11x=-x+112 | | -9x-107=3x+73 | | 3x-123=9x+57 | | -7x-101=3x+99 | | 8x-35=69+12x | | 24x+4=6 | | 4a+3b-2c= | | 10-x=8x-10 | | 4=-4x+3x+9 | | x+42x=24 | | X^2/4-x=15 | | 8x+13y=130whatisx+y | | X-3-4x=27 | | z=7a/9*4/2a | | 2y-18/6=4y+3 | | C-2=3c+24 | | y^2+16y+48=0 | | -3x+4=27 | | -14=-7r-7 | | 9=-7+4-6k | | 6856.9-6978.0= | | 10x-1=4x-31 |